Β‐hydroxy‐β‐methyl butyrate promotes leucine metabolism and improves muscle fibre composition in growing pigs. Issue 5 (15th July 2018) - Duan, Yehui H.; Zeng, Liming M.; Li, Fengnan N.; Kong, Xiangfeng F.; Xu, Kang; Guo, Qiuping P.; Wang, Wenlong L.; Zhang, Lingyu Y.
Abstract: The aim of this study was to investigate the effects of excess leucine (Leu) vs. its metabolites α‐ketoisocaproate (KIC) and β‐hydroxy‐β‐methyl butyrate (HMB) on Leu metabolism, muscle fibre composition and muscle growth in growing pigs. Thirty‐two pigs with a similar initial weight (9.55 ± 0.19 kg) were fed 1 of 4 diets for 45 days: basal diet, basal diet + 1.25% L‐Leu, basal diet + 1.25% KIC‐Ca, basal diet + 0.62% HMB‐Ca. Results indicated that relative to the basal diet and HMB groups, Leu and KIC groups exhibited increased Leu concentrations and decreased concentrations of isoleucine, valine and EAAs in selected muscle ( p  <   0.05) and had lower mRNA levels of MyHC I and higher expression of MyHC IIx/IIb ( p  <   0.05), and there was no significant difference between the basal and HMB‐supplemented groups. Moreover, the mRNA expression levels of AMPKα and UCP3 were higher but the myostatin mRNA levels were lower in the soleus muscle of the HMB group than those from other groups ( p  <   0.05). These findings demonstrated that doubling dietary Leu content exerted growth‐depressing effects in growing pigs; dietary KIC supplementation induced muscular branched‐chain amino acid imbalance and promoted muscle toward a more glycolytic phenotype; while dietary HMB supplementation promoted the generation of more oxidative muscle types and increased muscle growth specially in oxidative skeletal muscle, and these effects of HMB might be associated with the AMPKα‐Sirt1‐PGC‐1α axis and mitochondrial biogenesis.